Structural Asymmetry and Chiroptical Activity of Chiral Antimony‐Halide Hybrids. Issue 23 (7th July 2022) - Wang, Zhiyu; Zhang, Zixuan; Sung, Herman H. Y.; Williams, Ian D.; Lu, Haipeng
Abstract: Chiral metal‐halide hybrids have aroused widespread attention owing to their chemical and structural versatilities as well as unique optoelectronic and spin‐dependent properties. Several recent experiments have shown that organic chirality results in circularly polarized absorption and emission from the inorganic metal‐halide subcomponent; however, the exact structure chirality transfer mechanism and structure‐optical‐activity relation remain elusive. Here, we demonstrate how chiral organic cations lead to local structural asymmetry in a new series of chiral antimony‐halide hybrids, including zero‐dimensional edge‐shared (0D, A4 Sb2 X10, A=( R )‐(+)‐α‐methylbenzylammonium ( R ‐MBAH + ) or ( R )‐(−)‐1‐cyclohexylethylammonium ( R ‐CHEAH + ), X=Br, I) and one‐dimensional corner‐shared (1D, A'2 SbX5, A'=( R )‐(+)‐α‐ethylbenzylammonium ( R ‐EBAH + ); X=Br, I). Structure analysis shows that organic ammoniums distort the antimony‐halide octahedra through asymmetric hydrogen bonding. The chiroptical activity is correlated with the exciton coupling strength, which can be tuned by the structural dimensionality. Our study unveils the molecular scale chirality transfer mechanism in these chiral metal‐halide hybrids. Abstract : This study reports six new chiral antimony halide hybrids, including four zero‐dimensional (0D, A4 Sb2 X10, A=( R )‐(+)‐α‐methylbenzylammonium ( R ‐MBAH + ) or ( R )‐(−)‐1‐cyclohexylethylammonium ( R ‐CHEAH + ), X=Br, I) and two one‐dimensional (1D, A'2 SbX5, A'=( R )‐(+)‐α‐ethylbenzylammonium ( R ‐EBAH + ); X=Br, I) compounds. The chirality transfer mechanism and structure‐activity relationship were revealed at the molecular scale by analyzing their structure and chiroptical properties.